Perencanaan Strategis Sistem Dan Teknologi Informasi Pada PT Bina Megah Indowood Berdasarkan Metode Ward And Peppard - Fathur Rachman; Erwin Soetomo; Yoppy Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2018)
PT Bina Megah Indoowood (BMI) is a private companies operating income wood manufacture with the main product wood flooring and wood decking. PT BMI have a vision of “become industrial manufacturing wood that supplies quality products all over the world with superiority wood Indonesia”. Business process now done by implementing reservations raw materials , and in the production by taking into account the quality and demand customers after finished last products sent to customers. Problem that happens in PT BMI today is a system companies are not integrated and the absence of data management and evaluation the company only in financial .This has resulted in of business process has been blocked , the data uncontrolled and the absence of evaluation of the company long term. Based on the results of the preparation of strategic planning the system and information technology producing a tools and guidance in develop systems and information technology. Strategic planning it uses ward and peppard as framework which will be documents produced strategic planning the system and information technologyKeywords: Strategic Plan, Information System, Information Technology, Ward and Peppard